Recent reforms of the urban housing system in central and east Europe - Thiesenhusen, William C. (Land Tenure Center, University of Wisconsin-Madison, 2000)
The urban housing system in most of Central and East Europe (CEE) is undergoing decentralization, deregulation, and privatization together with other basic changes due to the fall of the iron curtain, the demise of the Soviet Union, and the reinstitution of democracy. In most of the CEE, the urban housing sector is economically important, accounting for 10-20% of total economic activity. In view of its implications for land use, energy consumption, waste generation, and water pollution, it also has a significant effect on sustainability of development. A prime development need in the CEE, according to the World Bank, is to improve the performance of the urban housing sector for economic, social, environmental, and political reasons. This paper describes the urban housing model of the CEE before reform and analyzes changes to that model that began with the privatization reforms in the early 1990s. The paper details the strengths and weaknesses of the reforms and suggests that there are some resource distribution inequities that are accentuated under reform. It discusses the pricing issues in urban housing reforms, as well as the financing of urban housing, and briefly recounts matters related to mobility of labor, spatial issues of urban housing development, urban infrastructure, peripheral urban growth, and titling and property registration that have come about as state socialism is replaced by a more open market.
Keywords: Housing Economic aspects Europe, Eastern; Housing Economic aspects Europe, Central; Housing policy Europe, Eastern; Housing policy Europe, Central; Privatization Europe; Land tenure, Urban Europe